THE CORRELATION BETWEEN SPEAKING CLASS ANXIETY AND STUDENTS’ ENGLISH PROFICIENCY - Multi Yusan Dana; Dyah Aminatun (fsip.teknokrat.ac.id, 2022)
Speaking is an essential skill that students should master because it requires oral communication such as, grammar, vocabulary, pronunciation, fluency, and comprehension. This study aims to determine the correlation between speaking class anxiety and their English skills. The participants in this study were sixth semester students majoring in English Education, Universitas Teknokrat Indonesia which consisted of 39 students. This research technique uses quantitative research. The research instrument was that students were asked to fill out a questionnaire about speaking anxiety which was distributed via a google form link and then the data would be analyzed with the help of SPSS 15.0 and Ms Excel 2007. The questionnaire was adopted from the Public Speaking Class Anxiety Scale (PSCA). The questionnaire contains 20 questions related to anxiety problems in speaking class with 5 scale criteria starting from strongly agree, agree, neutral, disagree and strongly disagree. From the result of the correlation between speaking anxiety and English proficiency scores, it can be concluded that students with high level of speaking anxiety had lower EPT scores than student with lower speaking anxiety level.